Dinamika Populasi Cendana (Santalum album L.) Di Hutan Dan Kebun Di Pulau Timor Barat, Nusa Tenggara Timur-Indonesia - Yoseph Nahak Seran; Sudarto Sudarto; Luchman Hakim; Endang Arisoesilaningsih (Metamorfosa: Journal of Biological Sciences, 2020)
Sandalwood (Santalum album L.) is a endemic spesies of the Lesser Sunda Island (NTT), grows in deciduous forest or in private traditional plantation for centuries. Study aimed to evaluated profile dynamic structure population of sandalwood in forest and plantation in the district of South Central Timor (TTS) and North Central Timor (TTU). Population structure analysis was held by purposive sampling in eight sites comprised 87 plots. Plots size were 20x20 m2 (trees), 10x10 m2 (poles), 5x5 m2 (saplings), 2x2 m2 (seedlings). Variables observed in each plot were included density, stem diameter, height of free trunk (TBBC), height trees and saplings, crown quality and coverage. Data were analyzed by qualitative descriptively and multivariate statistics. Results showed that population structure of sandalwood varied spatially in all study sites in two district, especially density of seedlings and saplings in plantations and forests. Sandalwood trees density ranges from 0-23 ind.ha-1, poles phase 80-322 ind.ha-1, saplings phase 60-1,289 ind.ha-1, while the seedlings phase is very dominant 2,000-27,813 ind.ha-1. Higher saplings and poles density were found in two sites of TTU plantation and forest or a TTS forest. Farmer in two districts successfully cultivated sandalwood in plantation shown by similar growth quality with those of forest trees. Keywords: Forest, NTT, population structure, plantation, sandalwood